Settlement ecology of Bronze Age Transylvania - Quinn, Colin P. (Frontiers in Human Dynamics, 2024)
The Bronze Age was a time of technological, socioeconomic, and political transformation in Europe. Since Bronze Age socioeconomic institutions were rooted in the landscape, they can be investigated using a settlement ecology approach to how people positioned themselves relative to the environment and each other. Transylvania is home to a rare combination of mineral resources, trade infrastructures, and productive agropastoral land, all of which were critical to Bronze Age societies. This study combines size-and rank-size analyses to suggest that there were several shifts in how people positioned themselves across settlements in Transylvania during the Bronze Age. This research contributes to a broader understanding of the factors that inform where people chose to settle down and the consequences those decisions have on the development of social, economic, and political institutions.